Circulating miR-448 acts as a potential diagnostic biomarker for multiple myeloma. Issue 1 (31st December 2022) - Chen, Dan; Chen, Teng; Wang, Lihong; Zhang, Zhihua; Xing, Enhong
ABSTRACT: Objective: The current diagnostic methods for multiple myeloma (MM) include bone marrow aspiration and biopsy, which are not only complicated but also invasive, causing great pain to patients. Micro ribonucleotides (miRNA) exist stably in circulating plasma and could be easily detected, making them promising specific diagnostic markers for MM. Methods: The expression of plasma miR-448 in MM patients was detected by real-time quantitative PCR analysis. Spearman correlation was used to analyze correlations between miR-448 expression and various clinic pathological characteristics of MM patients. The ROC and the AUC (95% confidence interval) were exploited to evaluate the potential of miR-448 acting as a diagnostic marker for MM patients. Results and discussion: In this study, we found that the expression level of miR-448 in patients with MM was significantly higher than that in normal people and showed statistically differential expression in different stages of MM. Besides, we observed that the abundance of miR-448 in the plasma of newly diagnosed MM patients was positively correlated with the proportion of plasma cells (PC) in the bone marrow and the concentration of serum M protein (MP), respectively. In addition, ROC analysis demonstrated the sensitivity and specificity of the diagnostic value of miR-448 for MM are 92.90% and 87.50%, respectively. Conclusion: Taken together, these results indicated that miR-448 may serve as a potential molecular diagnostic marker for MM.